Firms’ training processes and their apprentices’ education success - af Burén, Pontus [Verfasser]; Schweri, Jürg [Verfasser] (My University, 2024)
„In many European countries, firms engage heavily in the training of apprentices. The literature has investigated why firms provide such training, but almost no em pirical evidence exists on how firms train and shape their apprentices’ education outcomes. We investigate this question by estimating a training production func tion with employer-employee linked data on more than 3,700 Swiss firms and their 9,500 apprentices. Using measures derived from work psychology, we test whether apprentices are more likely to successfully complete training in standard time when they are trained in firms with better training processes. We find that apprentices are more successful in firms that assign tasks that make them find own solutions and that are more varied. We find only weak evidence for the hypothesis that the association of good training processes and education success is due to the assortative matching of good apprentices with good firms. We further show that our results are robust to di↵erent model specifications and formal sensitivity tests, suggesting an important role of firms and their training processes for apprentices’ education success.“ (authors‘ abstract; BIBB-Doku)

„Trotz der grossen Bedeutung der dualen beruflichen Grundbildung im Schweizer Bildungswesen wissen wir noch relativ wenig über die Rolle der unterschiedlichen Ausbildungsbedingungen in den Betrieben für den Ausbildungs- und Laufbahnerfolg der Lernenden. Im vorliegenden Projekt wird erstens untersucht, ob die Ausbildungsbedingungen im Lehrbetrieb sich auf einen erfolgreichen Lehrabschluss der Lernenden auswirken, also auf Lehrvertragsauflösungen sowie (Miss-)Erfolg am Qualifikationsverfahren. Zweitens wird der Einfluss der Ausbildungsbedingungen auf die Aufnahme weiterer Ausbildungen (z.B. Berufsmaturität und Fachhochschule) sowie den erfolgreichen Arbeitsmarkteintritt analysiert. Das Projekt verbindet die Forschungsliteraturen zur Ausbildungstätigkeit von Betrieben einerseits und zu den Übergängen von Lernenden im Bildungswesen beziehungsweise in den Arbeitsmarkt andererseits, um Hinweise auf besonders förderliche Ausbildungsbedingungen in den Lehrbetrieben zu gewinnen.“ (Autorenreferat; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 3.2 Unternehmen und Behörden; G 1.3.3.1 Qualifikationsverwertung; 370; Betriebliche Berufsausbildung; Ausbildungsbetrieb; Lernbedingungen; Ausbildungsqualität; Einflussfaktor; Ausbildungsabschluss; Ausbildungserfolg; Schweiz